Draw-A-Science-Comic: exploring children’s conceptions by drawing a comic about science - Lamminpää Jaakko; Vesterinen Veli-Matti; Puutio Katja (Routledge, 2022)
Background: Draw-A-Scientist Test (DAST) has been one of the most used instruments to study conceptions of scientists and science. It has been especially useful for charting the conceptions of younger children who might lack the skills to express themselves in writing. However, recent studies suggest that instead of children’s conceptions of the appearance of scientists, their conceptions about the activities are more crucial in shaping children’s attitudes towards science. Purpose: This study describes a new instrument, Draw-A-Science Comic (DASC), and examines the advantages and disadvantages of using a comic as a tool to collect data about children’s conceptions of scientists and science. Sample: A total of 104 children aged 8 to 13 drew a comic while attending university’s science camps during the summer of 2017 and 2018. Design and methods: Participants drew a comic about how science is made. The analysis of the drawings was based on four main categories: scientific activities, locations of research, appearance of scientists, and emotions and attitudes. Instances for each category were calculated by two researchers independently. Qualitative overviews of the categories and the methods used to convey information were formed. Results: The children used sequential pictures to depict actions and processes, speech bubbles to depict dialogue between characters as well as text captions to provide additional details and clarifications. By drawing comics children were able to have more detailed illustrations of scientific activities than with a single picture. The sequential narratives were also used to depict emotions and attitudes related to science. Conclusions: In contrast to DAST, the DASC provides information about children’s conceptions and stereotypes regarding scientific activities even without the use of additional or more explicit prompts.